Disassembly and reconstitution of a membrane-microtubule complex (The Rockefeller University Press, 1984)
The cell membrane of the unicellular algae Distigma proteus is associated with arrays of parallel microtubules. Fragments of the membrane-microtubule complex have been isolated and partially purified. The microtubules were stable in vitro at room temperature as well as at 0 degree C, but were specifically and rapidly disassembled by Ca2+. After removal of all endogenous microtubules, the membrane-microtubule complex could be reassembled from brain microtubule protein and denuded Distigma membrane fragments. The readded microtubules bound in a fixed orientation, and only to those regions of membrane that are normally associated with microtubules in vivo.